Exploring lecturers’ goal-setting using a coaching framework - Anna Carissa Rozzo (International Journal of Evidence Based Coaching and Mentoring)
This paper presents a small-scale study aimed at exploring how academic staff articulate professional goals. Methods include semi-structured interviews guided by Whitmore’s (2009) GROW model and analysed via reflexive thematic analysis. Methodological parallels between coaching and qualitative interviewing are discussed. The author describes in nuanced detail the motivation for and attributes of participants' goals through expressed patterns of meaning. Overall, the study highlights the potential efficacy of integrating coaching tools into qualitative research methodologies.